Two-dimensional effects in laser-created plasmas measured with soft-x-ray laser interferometry - Shlyaptsev, V. N., author; Moon, S. J., author; Marconi, M. C., author; Kanizay, K., author; Hammarsten, E. C., author; Jankowska, E., author; Rocca, Jorge J., author; Filevich, J., author; American Physical Society, publisher (Colorado State University. Libraries, 2003)
Soft-x-ray laser interferograms of laser-created plasmas generated at moderate irradiation intensities (1×1011-7×1012 W cm-2) with λ = 1.06 μm light pulses of ~13-ns-FWHM (full width at half maximum) duration and narrow focus (~30 μm) reveal the unexpected formation of an inverted density profile with a density minimum on axis and distinct plasma sidelobes. Model simulations show that this strong two dimensional hydrodynamic behavior is essentially a universal phenomena that is the result of plasma radiation induced mass ablation and cooling in the areas surrounding the focal spot.